Strategic vocabulary learning in vocabulary list learning: insights from EFL learners in Thailand - Panmei, Benjamin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Considering the number of class hours and the variety of learning materials provided in an EAP course at a university, the frequently estimated number of words that EFL students must master to function in English appears excessive. Recently, though, vocabulary list learning has evolved as an alternate approach to addressing such concerns. The current research investigated the strategic vocabulary learning that EFL students developed during word list learning. A list of 500 A1-A2 academic words divided into 10 sets was compiled and incorporated into a 10-week EAP English vocabulary course. The vocabulary acquisition of students was evaluated using weekly vocabulary tests (consisting of the words learned each week) and a final vocabulary exam (involving all the words in the 10 vocabulary sets). At the completion of the learning, quantitative and qualitative surveys were administered. The results of a mixed-method analysis revealed 1) memory, selective attention, learning words through use, and dictionaries as the most frequently used strategies; 2) shared learning strategies between male and female students, except for taking notes and visual repetition strategies; and 3) the efficacy of the infrequently used strategies in EFL students' vocabulary acquisition. The findings of the study call for the incorporation of explicit VLS instructions and training into students' word list learning, as well as the evaluation of how long words acquired by students will remain in their memories; continuous monitoring and evaluation; and teachers' continuous technical and emotional support during word list learning.